Autologous Micro-Fragmented Adipose Tissue as Stem Cell-Based Natural Scaffold for Cartilage Defect Repair. Issue 12 (December 2019) - Xu, Tengjing; Yu, Xinning; Yang, Quanming; Liu, Xiaonan; Fang, Jinghua; Dai, Xuesong
Osteoarthritis (OA) poses a tough challenge worldwide. Adipose-derived stem cells (ASCs) have been proved to play a promising role in cartilage repair. However, enzymatic digestion, ex vivo culture and expansion, with significant senescence and decline in multipotency, limit their application. The present study was designed to obtain micro-fragmented adipose tissue (MFAT) through gentle mechanical force and determine the effect of this stem cell-based natural scaffold on repair of full-thickness cartilage defects. In this study, ASCs sprouted from MFAT were characterized by multi-differentiation induction and flow cytometry. Scratch and transwell migration assays were operated to determine whether MFAT could promote migration of chondrocytes in vitro. In a rat model, cartilage defects were created on the femoral groove and treated with intra-articular injection of MFAT or PBS for 6 weeks and 12 weeks ( n = 12). At the time points, the degree of cartilage repair was evaluated by histological staining, immunohistochemistry and scoring, respectively. Two unoperated age-matched animals served as native controls. ASCs derived from MFAT possessed properties to differentiate into adipocytes, osteocytes and chondrocytes, with expression of mesenchymal stem cell markers (CD29, 44, 90) and no expression of hematopoietic markers (CD31, 34, 45). In addition, MFAT could significantly promote migration of chondrocytes. MFAT-treated defects showed improved macroscopic appearance and histological evaluation compared with PBS-treated defects at both time points. After 12 weeks of treatment, MFAT-treated defects displayed regular surface, high amount of hyaline cartilage, intact subchondral bone reconstruction and corresponding formation of type I, II, and VI collagen, which resembled the normal cartilage. This study demonstrates the efficacy of MFAT on cartilage repair in an animal model for the first time, and the utility of MFAT as a ready-to-use therapeutic alternative to traditional stem cell therapy.